Remember Me: Instagram, Selfies and Libraries. Issue 1 (2nd January 2020) - Budge, Kylie
ABSTRACT: While selfies continue to be characterised as part of a narcissistic moment in current history, when embedded as part of a library engagement project, they convey a wealth of nuanced material about their subjects, the role of the library, and perceptions about memory. Social photography, through applications such as Instagram, can reveal much about the social and cultural life of a place and its people and in turn, generate insights into what is valued. Yet few studies have focussed on libraries and Instagram, and almost none to date have examined the public library context. This article examines publicly-generated Instagram data created during a large library project in Australia to argue that the role of the library as memory collector and shaper of histories about people and place is critical to the exchange that occurred via way of selfies. Photographic portraits of the self – intimate and personal digital objects – are eagerly exchanged in turn for an opportunity to be remembered and for participating in a project that assembles and shapes public memory. Findings suggest that social photography projects containing intersections of people, libraries and memorialising a moment in time are powerful ways in which library publics can be engaged.